Akathisia superimposed to Hashimoto’s encephalopathy in an old lady: Akathisia superimposed to HE - Isik, Ahmet Turan; KAYA, DERYA; Altunkalem Seydi, Kubra (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Hashimoto’s encephalopathy (HE) is a rare clinical entity that is associated with encephalopathy with alteration of consciousness, presence of high levels of antithyroid antibodies, and exclusion of other suspected etiologies. Methods: We describe a 60-year old lady who had been followed up for about 5 years for possible Alzheimer’s disease plus Parkinson’s disease and presented with akathisia overlapping a progressive encephalopathy compatible with the diagnosis of HE. Results: Initial steroid therapy had shown no clinical benefit, whereas a mild to moderate improvement in clinical condition was observed after a 5-day course of plasmapheresis. Conclusions: Given this case, it is clear that this challenging yet treatable clinical syndrome should be considered even in older patients. Furthermore, side effects such as akathisia should also be considered when starting antipsychotic treatment, particularly in patients with an unclear diagnosis. The patient is noteworthy due to the extremely rare occurrence of HE presenting with akathisia, especially in the elderly.